Quality of Contraceptive Use and Women's Paid Work and Earnings in Peri-Urban Ethiopia. Issue 1 (2nd January 2020) - John, Neetu A.; Tsui, Amy O.; Roro, Meselech
Abstract : Economic and reproductive empowerment mutually reinforce each other. However, while many studies have examined the importance of economic empowerment for reproductive empowerment, few have investigated the reverse relationship, especially in Sub-Saharan Africa. This study uses retrospective contraceptive-use history and panel data from two time points from a peri-urban community in Ethiopia to explore the impact of quality of contraceptive use as measured by duration of use and type of method on a woman's ability to participate in the labor force, receive payment for work, and contribute to family income. Multivariate regression models were implemented based on the nature of the outcome variable. Women who reported more consistent use had statistically significant higher odds of working in the labor force and receiving cash payments. The findings illustrate the critical role of contraceptive use in enabling women to participate in the labor force and receive payment for their work.